Minimally Invasive Sacroiliac Joint Fusion: One-Year Outcomes in 40 Patients - Donald Sachs; Robyn Capobianco (Advances in Orthopedics)
Background. SI joint pain is difficult to diagnose due to overlapping symptoms of the lumbar spine, and until recently, treatment options have been limited. The purpose of this retrospective study is to report on the safety and effectiveness of MIS SI joint arthrodesis using a series of triangular, porous plasma coated implants in patients refractory to conservative care. Methods. We report on the first 40 consecutive patients with one-year follow-up data that underwent MIS SI joint fusion with the iFuse Implant System (SI-BONE, Inc., San Jose, CA) by a single surgeon. Medical charts were reviewed for demographics, perioperative metrics, complications, pain scores, and satisfaction. Results. Mean age was 58 years (range 30–81) and 75% of patients were female. Postoperative complications were minimal and included transient trochanteric bursitis (5%), facet joint pain (20%), and new low back pain (2.5%). There were no reoperations at one year. Mean pain score improved from 8.7 (1.5 SD) at baseline to 0.9 (1.6) at 12 months, a 7.8-point improvement (P<.001). Patient satisfaction was very high. Conclusions. The results of this case series reveal that MIS SI joint fusion using the iFuse Implant System is a safe and effective treatment option in carefully selected patients.